Methodology of System Management of the Supply Chain Based on the Leasing Process - Pavel G.Ryabchuk; Igor A.Baev; Anton S.Apukhtin; Svetlana S.Demtsura; Irina I.Pluzhnikova; Dmitry N.Ðšorneev; Andrei V.Fedoseev (International Journal of Supply Chain Management, 2019)
The development of leasing relations is based on the adequate methodological basis for assessing the effectiveness of the leasing process. The purpose of our research is to describe the methodology for assessing and managing the leasing process taking into account the interests of the lessee and the factors of the external and internal environment. In our research leasing process is represented as an element of supply chain management. The main methods that we used in our research were the method of modeling cash flows of the enterprise - recipient and the method of discounting the cash flows generated with the participation of an industrial enterprise in the leasing process, the methodology for modeling the supply chain of an industrial enterprise. The proposed methodology is a universal tool for assessing and managing the leasing process, which includes the strengths of advanced methods for assessing the effectiveness of a leasing scheme for financing productive investments accumulated in scientific works of experts in the field of leasing and logistics. The proposed structure of strategic features based on a set of methods for assessing leasing activities, leasing potential and leasing climate allows an industrial enterprise to develop management strategies for the leasing process based on the performance. The methodology of assessment and management has practical value for a wide range of organizations that are considering the possibility of technological re-equipment of industrial production in the context of platform business networks, as well as the improvement of supply chain management.